Network Monitoring Support System (NMSS): performance evaluation tools and testing / Mohd Nazri Mustafa - Mustafa, Mohd Nazri (2016)
Network Monitoring Support System (NMSS) is all-inclusive applications has the capability to monitor and manage NCO network performance such as video conferencing and other network services. Typical components in network management systems are Network Monitoring System (NMS), Aset Management, Helpdesk System and Patch Management System. This thesis demonstrates an evaluation of testing parameters used for Network Monitoring Support System (NMSS), with emphasis on testing bandwidth on utilization of video conferencing to proof that the application is reliable in our organization. Results analysis were obtained from several network devices application on performance monitoring system implemented and tested in selected areas in Malaysia.